Support to the economic development of Vojvodina from Hungary - Gabrić-Molnar, Iren; TerézКovács (Anali Ekonomskog fakulteta u Subotici, 2020)
In accordance with the provincial economic developmental program, the Hungarian community in Vojvodina assembled an economic developmental strategy in 2015, which not only coordinates with the objectives of the Serbian Government, but also with that of the Hungarian Government, to be specific to provide financial support to the region. The present study introduces how financial support was realized in the time period of 2016-2018. As a source for data collection, in-depth interviews were conducted and data provided by the Prosperitati Foundation, which coordinates the financial resources from Hungary, was also considered. The Prosperitati Foundation was in contact with the applicants/competitors, realized the process of evaluation, signed the contract, transferred the sum of financial support as well as oversaw the process of control. According to the basic idea of the program, only entrepreneurs with dual-citizenship (Serbian and Hungarian) could apply for the financial support, mostly farmers and small-sized entrepreneurs. In case of successful application, during the first period of the program, entrepreneurs could receive a maximum amount of 1 million RSD. The own share was 20%, and pre-financing was established. Along the huge amount of interest, the output of the three years is more than 10.000 supported entrepreneurs/farmers, several hundred hectares of purchased land, several hundreds of rural houses and financial assistance of 250 million EUR. The main objective of the Hungarian Government was to support the middle and lower-middle class of Hungarians in Vojvodina. In the second phase of the program, along the small-sum subsidies large capital investments and technological developments were initiated for the purpose of establishing more workplaces.